The Effect of microparticulate from whey protein concentrates on the characteristics of fresh cheese - Bejarano-Toro, Edinson- Eliecer; Rodríguez-Sandoval, Eduardo; Sepúlveda-Valencia, José-Uriel (Revista de Ciencias Agrícolas, 2023)
Whey, obtained from cheese manufacturing, has a significant environmental impact due to its organic load and volume produced. Therefore, validating technologies that allow its valorization due to its content of ingredients of high nutritional or functional value becomes relevant for the dairy industry. Microparticulate whey protein (MWP) has been used to produce cheeses and has the potential to improve process performance. We seek to develop and optimize the characteristics of a MWP to be used to make white cheese. For this, factors such as temperature, from 73 to 93°C, and retention time from 3 to 17 min of the heat treatment were evaluated. We assessed zeta potential, particle size, color, protein retention coefficient, and cheese yield as response variables using a response surface design with 14 experiments. Optimum conditions were 93°C for 5.4 min retention. In the white cheese production, two inclusion percentages were tested: 3 and 5% (w/w); and the impact on characteristics like yield, protein retention, and texture was evaluated with respect to a control cheese that was not added with MWP. We found that 3% inclusion is more suitable because it keeps textural characteristics closer to traditional cheese. The MWPs add value to whey and cheese by improving performance and enabling the retention of proteins of high biological and nutritional value.